Facile synthesized carbon dots for simple and selective detection of cobalt ions in aqueous media. Issue 1 (31st December 2022) - Alkian, Ilham; Sutanto, Heri; Hadiyanto, B; Prasetio, Adi; Aprimanti Utami, Bella
Abstract: A simple method was demonstrated for detecting cobalt ions based on the fluorescence quenching of carbon dots (CDots). The best quantum yield for CDots synthesized by microwaving lime and methanolamine is 49.42%. The detection range of this research is 0–200 μM with a detection limit of 1.63 μM, respectively. Because of the interaction between functional groups and metal ions, CDots made from lime are more sensitive to cobalt ions than CDots made from other oranges. This study presents a platform for demonstrating the high sensitivity of cobalt ion sensing using CDots. Overall, these findings suggest that functional groups influence the quantum yield and detection limit of CDots, which will be beneficial for the further development of CDots for sensing purposes.